Tailoring structural and thermal properties of neodymium hafnium-zirconium oxide nano particles (Nd2(Hf1−xZrx)2O7; x = 0.2, 0.5) for thermal barrier coatings - Jittu Varghese Kurian; M R Radhakrishna Panicker; Job P A; Sabu Thomas; Asaletha R (Nano Express)
This study examines the effect of the doping concentration (x) of substituting elements Hafnium (Hf) and Zirconium (Zr) in a Neodymium (Nd) based oxide matrix on its structural and thermal properties. The selection of these dopants is based on their varying ionic radii and atomic weights, which are anticipated to affect lattice distortion, oxygen vacancy formation, and thermal properties. Characterization techniques were utilized to analyze the changes in structural, morphological, and thermal properties resulting from doping. X-ray diffraction (XRD) analysis revealed a weakly ordered pyrochlore structure in both samples, offering significant insights into crystal structure and phase. Subsequent to XRD analysis, Raman spectroscopy is utilized to gain deeper insights into phase and lattice disorder attributed to oxygen vacancies, revealing a greater concentration of oxygen vacancies in the x = 0.5 composition relative to the x = 0.2 variant. Scanning Electron Microscopy (SEM) was utilized to analyze the surface morphology and verify the existence of pores. The BET study illustrates the development of porous-agglomerated particles for both samples. The BET study indicated an increase in pore volume, porosity, and specific surface area for the Nd _2 (Hf _1−x Zr _x ) _2 O _7 (x = 0.5) sample. Furthermore, we observe exceptionally low thermal conductivity of 0.44 W m ^−1 K ^−1 for the Nd _2 (Hf _1−x Zr _x ) _2 O _7 (x = 0.2) sample at 350 °C. Overall, this study describes the development and characterization of novel Nd _2 (Hf _1−x Zr _x ) _2 O _7 (x = 0.2, 0.5) samples with reduced thermal conductivity, offering pathways for optimizing materials for thermal barrier coating applications.